Penerapan flipped classroom dalam pembelajaran tata bahasa: Sebuah tinjauan pustaka tematik - Rullytama, Muhammad Fikri; Hafirdin, Evan Kamil; Darmawangsa, Dante (Aksara: Jurnal Bahasa dan Sastra, 2023)
The development of information technology in language learning has encouraged teachers to switch from traditional learning methods. One of the learning methods that utilize information technology is the flipped classroom method which combines learning methods in the classroom and outside the classroom. This method can also be applied in learning grammar. This study aims to identify the benefits and constraints of implementing the flipped classroom in teaching grammar in foreign language classes. This research is a literature review using the thematic literature review method. The data sources for this literature review are 29 research articles found in the Google Scholar, ResearchGate and FreeFullPDF databases based on keywords and criteria determined by the researchers. The results of the thematic literature review show that the application of the flipped classroom method has a positive impact on students' mastery of grammar, encourages teachers to be more creative in making materials, and makes students more independent, confident and active in class discussions. However, the implementation of this method has several obstacles, including the problem of internet network stability, the preparation of teaching materials which is quite time-consuming, and the difficulty of adapting the application of this method for both students and teachers.Keywords: Flipped classroom, grammar, thematic literature review